DAUHRUD- A CONCEPTUAL REVIEW - Jasobanta Dansana; Abhijit B. Patil (International Journal of Applied Ayurved Research, 2020)
Ayurveda is a science of life. To maintain Swastha Rakshana, Ayurveda has emphasized the need of Dincharya, Rutucharya etc. In the same manner to get a healthy and prosperous child, Ayurveda advocates the concept of Garbhini Paricharya. Mother’s diet and activities performed during the period of pregnancy reflect on the fetus. The chief characterstics features in 4thmonth is the mother expressing the nature of child through her taste preferences behaviour. This condition is called as “Dauhrid Awastha” (Longings or Pica of mother). The Dauhruda Bhawas of fetus expressed through the mother desire. If these desires are not being fulfilled, the fetus will affect and produce deformity in new born. We must have to complete her all longings.